2013
DOI: 10.1007/s10995-013-1399-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Effectiveness of Maternal Influenza Vaccination During Pregnancy: A Review of the Evidence

Abstract: Influenza vaccine is universally recommended for pregnant women during any trimester of pregnancy. In light of this recommendation, a comprehensive literature review was conducted to examine the available evidence regarding influenza vaccine efficacy and effectiveness during pregnancy. A comprehensive Medline search identified potentially relevant articles published between January 1, 1964 and February 1, 2013. Articles were selected that specifically evaluated the efficacy and effectiveness of maternal influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 45 publications
1
21
0
1
Order By: Relevance
“…The present study also identified no difference between the clinical severities of influenza A versus B. [17].…”
Section: Discussionsupporting
confidence: 54%
“…The present study also identified no difference between the clinical severities of influenza A versus B. [17].…”
Section: Discussionsupporting
confidence: 54%
“…Stx2 injection or oral administration of an Stx2-producing EHEC strain. Because vaccination of pregnant women has been demonstrated to be a good approach to control endemic diseases (46,47), and considering that in certain regions of Argentina incidences are as high as 55/100,000 HUS cases and EHEC infections are endemic (7,48), we suggest that BLS-Stx2B could be useful to control disease in areas of endemicity through vaccination strategies in female adults.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination of pregnant women has been demonstrated to be a good approach to control endemic diseases [35,36]. According to our results, we suggest that the vaccination of with ␥-Int C 280 and EspB proteins could be useful to control disease in areas where infections with E. coli O157:H7 are endemic.…”
Section: Discussionmentioning
confidence: 54%